Prevalence survey of selected bovine pathogens in water buffaloes in the north region of Brazil - Silva, Jenevaldo Barbosa da [UNESP]; Santos, Priscilla Nunes dos; Castro, Gustavo Nunes de Santana; Fonseca, Adivaldo Henrique da; Barbosa, José Diomedes (Hindawi Publishing Corporation, 2014)
Although the largest buffalo herd in the occident is in the north region of Brazil, few studies have been conducted to assess the prevalence of selected parasitic diseases in buffalo herd. The present study was therefore conducted to investigate the epidemiological of Toxoplasma gondii, Neospora caninum, Anaplasma marginale, Babesia bigemina, and Babesia bovis in water buffaloes in the north region of Brazil. A total of 4796 buffalo blood samples were randomly collected from five provinces and simultaneously analyzed by the IFAT and ELISA. The serological prevalence of T. gondii and N. caninum was 41.3% and 55.5% in ELISA and 35.7% and 48.8% in IFAT, respectively. The overall prevalence of A. marginale, B. bovis, and B. bigemina was 63%, 25%, and 21% by ELISA and 50.0%, 22.5%, and 18.8% by IFAT, respectively. This study shows valuable information regarding the serological survey of selected bovine pathogens in water buffaloes in the north region of Brazil which will likely be very beneficial for the management and control programs of this disease.